End-of-Life Care in the Neonatal Intensive Care Unit: Experiences of Staff and Parents - Cortezzo, DonnaMaria E.; Sanders, Marilyn R.; Brownell, Elizabeth A.; Moss, Kerry (American Journal of Perinatology, 2015)
Objective The aim of the study is to determine the perceptions of end-of-life care practices and experience with infants who have died in the NICU among neonatologists, advanced practitioners, nurses, and parents, and also to determine perceived areas for improvement and the perceived value of a palliative care team.Study Design This descriptive, exploratory cross-sectional study using surveys consisting of 7-point Likert scales and free response comments was sent to all neonatologists (n = 14), advanced practitioners (n = 40), and nurses (n = 184) at Connecticut Children's Medical Center's neonatal intensive care units (NICUs) in April 2013 and to all parents whose infants died in these NICUs from July 1, 2011, to December 31, 2012 (n = 28).Results The response rates were 64.3% for physicians; 50.0% for practitioners; 40.8% for nurses; and 30.4% for parents. Most providers reported they feel comfortable delivering end-of-life care. Bereavement support, debriefing/closure conferences, and education did not occur routinely. Families stressed the importance of memory making and bereavement/follow-up. Consistent themes of free responses include modalities for improving end-of-life care, inconsistency of care delivery among providers, and the importance of memory making and follow-up.Conclusion End-of-life experiences in the NICU were perceived as variable and end-of-life practices were, at times, perceived as inconsistent among providers. There are areas for improvement, and participants reported that a formalized palliative care team could help. Families desire memory making, follow-up, and bereavement support.
Keywords: end-of-life experiences; end-of-life care; neonate